The quest for God & the good life : Lonergan's theological anthropology - Miller, Mark T. (UPCC book collections on Project MUSE., 2013)
Troubled by the Great Depression, two world wars, and modernity's challenges to religion, Bernard Lonergan attempted to do for our age what Thomas Aquinas did for his: to integrate the best of secular and sacred learning and thus further the Catholic tradition of using both faith and reason to advance the common good and participate in God's work of salvation. Drawing on modern advances in the natural sciences, economics, history, and psychology, as well as ancient and medieval philosophy and theology, Lonergan's work is highly fruitful but exceedingly complex. This book provides a basic yet broad introduction to Lonergan's thought in particular and Catholic theology in general.\Mark T. Miller's approach is a theological anthropology organized into three main categories, "progress," "decline," and "redemption," which transpose the traditional concepts of nature, sin, and grace into a contemporary social and historical context. Progress is driven by the natural human desire for God. Decline is a downward spiral of violence and suffering caused by sin's perversion of the good, natural desire. Redemption is God's gift of God's self that fulfills our natural desire and becomes the foundation for authentic human living.\Throughout this introductory text, progress, decline, and redemption constitute a systematic framework for examining the central terms of Catholic theology, as well as key notions in Lonergan's theology. The book provides a firm foundation for students of Lonergan as well as anyone interested in understanding Catholic theology and applying it to ministry, education, and other fields.